Analyzing manufacturing sector and selected development challenges: A panel data analysis. (15th November 2021) - Halkos, George; Moll de Alba, Jaime; Todorov, Valentin
Abstract: The importance of manufacturing as a main determinant of economic growth has been explored extensively in the literature considering manufacturing as the engine of economic growth. In our study, a new database covering 117 countries for 1995–2017 containing four indicators, namely manufacturing value added share in GDP, growth of GDP, manufacturing energy intensity, and UNIDO's Competitive Industrial Performance score is constructed. Relying on this dataset and the Granger causality tests the paper investigates the effect of economic growth, energy intensity and the competitiveness index on manufacturing value added. Applying adequate econometric methods the effect of this set of variables on the relative importance of manufacturing in the economy as a whole measured by the share of MVA in GDP (MVAsh) is analyzed. An inverted U shape is verified with different turning points between static and dynamic analyses in the full sample, as well as in industrialized countries and emerging and developing countries separately, with turning points all within samples. Energy intensity has negative effect in most of the cases while CIP has positive effect with high magnitudes. The rate of adjustment is high. Highlights: We estimate the adjustment rate and main indicators effect on manufacturing sector. Static and dynamic panel specifications are proposed modelling MVA share and growth. We explore energy intensity effect on selected indicators of industrial development. We use for first time in such specifications manufacturing energy intensity. UNIDO's Competitive Industrial Performance score is used for the first time.